Information Security for the Application of Methods for the Evaluation of the Administration of Revenues of Municipalities - Kirilov, Rosen; Emilova, Katya (Research Papers, 2011)
In the studios are considered information issues in the application of various assessment methods in the process of administering the revenues of municipalities. Trusts are known in theory and practice methods to evaluate and carry out a comparative analysis between them as the basis for determining sources of data. On this basis, the proposed indicators and systems of weight coefficients necessary for the evaluation of the administration of the income of the Commons. Along with this place and the issues for determination of a sample of the municipalities, on which to implement the evaluation methods. Experimental results show that the labour force survey is a possible source of data and is suitable for carrying out the comparative analysis and discovery of connections and relationships.